Manajemen Peserta Didik Untuk Meningkatkan Prestasi Siswa pada Madrasah Aliyah Negeri (MAN) Pacitan - Wahyu Suminar (IAIN Ponorogo, 2017)
Abstract: The researcher is intended to reveal (1) the implementation of the service, guidance, and control of student management in enhancing students’ achievement and (2) the development of students’ achievement based on students’ preference at State Islamic Senior Highschool (MAN) of Pacitan. This research is qualitative research which takes the setting at State Islamic Senior Highschool (MAN) of Pacitan. This research employed descriptive qualitative research design. The data collection techniques of the study were observation, in-depth interview, and documentation. The results of the study showed that (1) student management in enhancing students’ achievement at State Islamic Senior Highschool (MAN) of Pacitan involves three aspects, namely, service, guidance, and control with various learning activities which try to develop students’ potential, talent and interest in term of academic and non-academic competency in order to enhance students’ achievement, (2) the development of students’ achievement based on students’ preference at State Islamic Senior Highschool (MAN) of Pacitan is developed through multiple intelligence. The students, who have high intelligence and interested more in subject matter or academic competence, are facilitated with some activities like discussion, subject matter group, review of SKL and tutoring. Furthermore, the students, who possess high intelligence and interested more in non-academic competence, are facilitated with various outdoor activities, such as extracurricular like scouting, muhadhoroh, MTQ, PMR, UKS, Risma, theater, journalistic, KIR, music, calligraphy and sport.Abstrak: Penelitian ini bertujuan untuk mengetahui tentang pelayanan, pembinaan dan pengawasan manajemen peserta didik dalam meningkatkan prestasi siswa di MAN Pacitan? Serta megetahui pengembangan prestasi siswa berbasis preferensi peserta didik di MAN Pacitan. Penelitian ini merupakan bentuk pendekatan kualitatif dengan setting di MAN Pacitan yang menghasilkan data deskriptif kualitatif. Hasil penelitian ini adalah bahwa (1) manajemen peserta didik dalam meningkatkan prestasi siswa di MAN Pacitan mencangkup tiga aspek yakni pelayanan, pembinaan dan pengawasan dengan berbagai kegiatan di dalamnya yang berupaya mengembangkan potensi, bakat dan minat peserta didik dari segi akademis dan non akademis dengan tujuan untuk meningkatkan prestasi siswa. (2) Pengembangan prestasi siswa berbasis preferensi peserta didik di MAN Pacitan dikembangkan melalui multiple intellegence, peserta didik yang memiliki kecerdasan dan kegemaran lebih dalam hal mata pelajaran atau akademis diwadahi dengan kegiatan seperti diskusi dengan membentuk grup mata pelajaran, bedah SKL, dan bimbingan belajar lainnya. Sedangkan peserta didik yang memiliki kecerdasan dan kegemaran lebih di bidang non akademis diwadahi dengan berbagai kegiatan di luar kelas yaitu kegiatan ekstrakurikuler seperti Pramuka, Muhadhoroh, MTQ, PMR, UKS, Risma,Teater, Jurnalistik, KIR, Seni Musik dan Kaligrafi, dan Olah raga.